Prevalensi Anak Stunting di Kota Salatiga Tahun 2020 - Oktapianus Oktapianus; Dary Dary; Brigitte Sarah Renyoet (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: Stunting cases occur in several countries, especially poor and developing countries. Stunting is a growth disorder in children due to poor nutrition. Malnutrition occurs during the First 1000 Days of Life (HPK). The child's growth is disrupted so that the child will look short, and cognitive and motor development is hampered. The purpose of this research is to find out the prevalence of stunting children in Salatiga City.Methods: Cross-sectional descriptive method is used to describe the description of the phenomenon of stunting exposure by observing the population that occurs in Salatiga City in 2020. Data collection was obtained by measuring height and then the data was adjusted to PB / U or TB / U - 3 SD sd <- 2 SD (stunted) dan <-3 SD (severely stunted). The research data were then analyzed descriptively using Microsoft Excel and displayed in the form of tables and narratives. Data collection in this study was carried out in March-June 2021 in four sub-districts located in Salatiga City.Result: The results showed that the prevalence of stunting in Salatiga City in 2020 in children aged 0-60 months was 6,85%, the incidence of stunting was more common in males by 3,65%.Conclusion: The conclusion from this study, it is known that the prevalence of stunting in Salatiga City in 2020 reached 6.85%. The highest cases occurred in the male sex with a percentage of 3.65%. In terms of age, the highest incidence of stunting occurred in children aged over 25-60 months.